1978
DOI: 10.1007/bf01870392
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of cellular K+ accumulation from net Na+ transport by toad urinary bladder

Abstract: Summary.A number of published data suggest a variable stoichiometry between the rates of cellular potassium uptake and net sodium transport (JNa) across the urinary bladder of the toad. This problem was examined by simultaneously studying the iutracellular chemical activity of potassium (aK) with open-tip K+-selective microelectrodes and micropipets, and monitoring JNa by measuring the short-circuit current (SCC). When bathed in the short-circuited state with solutions containing an a• of 2.7 mrs, the mean + S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 79 publications
2
33
0
Order By: Relevance
“…These observations complement the results of recent studies of the intracellular fluids of toad urinary bladder, using K +-selective microelectrodes (DeLong & Civan, 1978, 1979, 1980 and using electron probe X-ray microanalysis . After incubation in K +-free media for 1 89 to 2 hr, the transporting cells of toad bladder lose only some 20% of their intracellular potassium (Robinson & Macknight, 1976a;Civan et al, 1980).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These observations complement the results of recent studies of the intracellular fluids of toad urinary bladder, using K +-selective microelectrodes (DeLong & Civan, 1978, 1979, 1980 and using electron probe X-ray microanalysis . After incubation in K +-free media for 1 89 to 2 hr, the transporting cells of toad bladder lose only some 20% of their intracellular potassium (Robinson & Macknight, 1976a;Civan et al, 1980).…”
Section: Discussionsupporting
confidence: 88%
“…Recent electronmicroprobe analysis of toad bladder is in qualitative agreement with previous estimates based on chemical analysis of mucosal cell scrapings, but indicates that 0022-2631/80/0057-0235 $01.40 9 1980 Springer-Verlag New York Inc. more sodium is actually gained by the transporting epithelial cells than had previously been estimated; the accumulation of sodium and loss of potassium are comparable in magnitude (Civan, Hall & Gupta, 1980). Thus, given the uncertainties of the experimental techniques, and the possibility that the stoichiometry of the pump might undergo modest changes even under physiologic conditions, the dissociation between the time courses of intracellular potassium activity and short-circuit current noted by DeLong and Civan (1978) might be consistent with the operation of a single Na-K rheogenic pump at the basolateral membrane.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Since epithelial cells contain more sodium than sartorius muscle fibres ai would not be expected to exceed 80-90 mm. On the other hand, values of 39-43 mm for ai found previously in frog and toad bladder (Kimura & Fugimido, 1977;DeLong & Civan, 1978) would seem to err on the other side, leaving a large osmotic deficit within the cells. DeLong & Civan (1979 have since reported ai values of 80 and 70 mm from experiments with double-and single-barrelled micro-electrodes respectively.…”
Section: Ion Activities In Frog Skinmentioning
confidence: 86%
“…This may be due to an ionic gradient through to tissue (Zeuthen, 1978) or to a difference in treatment of the tissue. It may also reflect the apparent compartmentalization ofintracellular potassium (DeLong & Civan, 1978) in epithelial tissues. The increase in a' found by us in the presence of amiloride although contrary to findings in toad bladder (MacKnight, Civan & Leaf, 1975) may occur in the rapidly exchanging potassium pool (MacKnight et al 1980) reported to have a lower potassium content than the slowly exchanging pool.…”
Section: Ion Activities In Frog Skinmentioning
confidence: 99%